AFM investigation of Martian soil simulants on micromachined Si substrates. - Vijendran, S; Sykulska, H; Pike, W (2007)
The micro and nanostructures of Martian soil simulants with particles in the micrometre-size range have been studied using a combination of optical and atomic force microscopy (AFM) in preparation for the 2007 NASA Phoenix Mars Lander mission. The operation of an atomic force microscope on samples of micrometre-sized soil particles is a poorly investigated area where the unwanted interaction between the scanning tip and loose particles results in poor image quality and tip contamination by the sample. In order to mitigate these effects, etched silicon substrates with a variety of features have been used to facilitate the sorting and gripping of particles. From these experiments, a number of patterns were identified that were particularly good at isolating and immobilizing particles for AFM imaging. This data was used to guide the design of micromachined substrates for the Phoenix AFM. Both individual particles as well as aggregates were successfully imaged, and information on sizes, shapes and surface morphologies were obtained. This study highlights both the strengths and weaknesses of AFM for the potential in situ investigation of Martian soil and dust. Also presented are more general findings of the limiting operational constraints that exist when attempting the AFM of high aspect ratio particles with current technology. The performance of the final designs of the substrates incorporated on Phoenix will be described in a later paper.